2021
DOI: 10.1038/s41366-021-00742-4
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-ablation of cardiac sodium channel Nav1.5 mitigates susceptibility to atrial fibrillation and improves glucose homeostasis under conditions of diet-induced obesity

Abstract: Background Atrial fibrillation (AF) is the most common sustained arrhythmia, with growing evidence identifying obesity as an important risk factor for the development of AF. Although defective atrial myocyte excitability due to stress-induced remodeling of ion channels is commonly observed in the setting of AF, little is known about the mechanistic link between obesity and AF. Recent studies have identified increased cardiac late sodium current (INa,L) downstream of calmodulin-dependent kinase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…25,39 This leads to enhanced sodium entry into the cell, elevation of intracellular sodium concentration and consequently increased calcium influx via the reverse mode of the sodium/calcium-exchanger NCX, promoting calcium-dependent proarrhythmic events. 35 Again, similar electrophysiological changes have been observed in obesity models, 31,42,43 although this has been less extensively investigated as compared to diabetes.…”
Section: Metabolic Changes Mitochondrial Dysfunction Oxidative Stress and Intracellular Ionic Dysregulationmentioning
confidence: 75%
“…25,39 This leads to enhanced sodium entry into the cell, elevation of intracellular sodium concentration and consequently increased calcium influx via the reverse mode of the sodium/calcium-exchanger NCX, promoting calcium-dependent proarrhythmic events. 35 Again, similar electrophysiological changes have been observed in obesity models, 31,42,43 although this has been less extensively investigated as compared to diabetes.…”
Section: Metabolic Changes Mitochondrial Dysfunction Oxidative Stress and Intracellular Ionic Dysregulationmentioning
confidence: 75%
“…The changes in calcium homeostasis in patients with AF or in AF animal models are similar to the changes in calcium dysregulation in Gal‐3‐treated HL‐1 cells; this finding suggests that Gal‐3 takes part in inflammation‐induced AF genesis. As shown in Figure 8, Gal‐3‐mediated Ca 2+ dyshomeostasis might be caused by the activation of CaMKII/RyR2 signalling, resulting in enhanced Nav1.5 and NCX and increased atrial ectopic activity 17,23,24 . Recent results revealed that a Nav1.5‐dependent elevation of sodium influx leads to CaMKII activation, which sequentially phosphorylates Nav1.5 and promotes sodium influx 25 .…”
Section: Discussionmentioning
confidence: 99%
“…5 atrial ectopic activity. 17,23,24 Recent results revealed that a Nav1.5-dependent elevation of sodium influx leads to CaMKII activation, which sequentially phosphorylates Nav1.5 and promotes sodium influx. 25 The frequency of atrial ectopic beats can predict adverse cardiovascular events and AF occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The diabetic, hypertrophied and failing heart is prone to atrial and ventricular arrhythmias, which are often related to activation of voltage-gated sodium channels (Na v 1.5 or Na v 1.8), facilitating the late sodium current and leading to sparks due to spontaneous release of calcium. [115][116][117][118] These abnormalities have been attributed to O-GlcNAcylation of Na v 1.5, as they are abolished following inhibition of UDP-GlcNAc. 119 Additionally, Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) is activated in the hypertrophied and failing heart and phosphorylates ion channels and transcription factors that are critical for hypertrophy, atrial arrhythmogenesis, oxidative stress and proinflammatory signalling.…”
Section: Cardiac Ions Channels and Arrhythmiasmentioning
confidence: 99%